Hippasteria falklandica Fisher 1940 - Mah, Christopher; Nizinski, Martha; Lundsten, Lonny (Zenodo, 2010)
HIPPASTERIA FALKLANDICA FISHER, 1940 Fisher, 1940: 125; Bernasconi, 1973: 287; Clark & Downey, 1992: 247; Stampanato & Jangoux, 2004: 6; McKnight, 2006: 97 Occurrence: Falkland Islands (=Islas Malvinas), northern Argentina, Marion and Prince Edward Islands region to south of Tasmania, approx. 49°S, 150°E. 225–1148 m. Material examined: None. Published as part of Mah, Christopher, Nizinski, Martha & Lundsten, Lonny, 2010, Phylogenetic revision of the Hippasterinae (Goniasteridae; Asteroidea): systematics of deep sea corallivores, including one new genus and three new species, pp. 266-301 in Zoological Journal of the Linnean Society 160 (2) on page 286, DOI:10.1111/j.1096-3642.2010.00638.x, http://zenodo.org/record/10114738